2016
DOI: 10.1109/tmag.2016.2580532
|View full text |Cite
|
Sign up to set email alerts
|

Write Error Rate of Spin-Transfer-Torque Random Access Memory Including Micromagnetic Effects Using Rare Event Enhancement

Abstract: Spin-transfer-torque random access memory (STT-RAM) is a promising candidate for the next-generation of random-access-memory due to improved scalability, read-write speeds and endurance. However, the write pulse duration must be long enough to ensure a low write error rate (WER), the probability that a bit will remain unswitched after the write pulse is turned off, in the presence of stochastic thermal effects. WERs on the scale of 10 −9 or lower are desired. Within a macrospin approximation, WERs can be calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…As is evident, probability distributions obtained from micromagnetic simulations can be very different from ones obtained from macrospin simulations. Average switching times obtained from micromagnetic simulations are always found to be lower than that obtained from macrospin simulations, in agreement with previous studies [33,34]. The probability distribution function (PDF) of t sw resulting from the thermal fluctuation has been described previously in terms of a skew-normal PDF, where the PDF is characterized by the mean, standard deviation, and skewness [30][31][32] or Pearson IV form [34].…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…As is evident, probability distributions obtained from micromagnetic simulations can be very different from ones obtained from macrospin simulations. Average switching times obtained from micromagnetic simulations are always found to be lower than that obtained from macrospin simulations, in agreement with previous studies [33,34]. The probability distribution function (PDF) of t sw resulting from the thermal fluctuation has been described previously in terms of a skew-normal PDF, where the PDF is characterized by the mean, standard deviation, and skewness [30][31][32] or Pearson IV form [34].…”
Section: Methodssupporting
confidence: 88%
“…Even within the macrospin approximation, attempts have been made to reduce the computational load by modeling variation of parameters in a multi-dimensional space in terms of linear analytical equations that describe the stochastic magnetization dynamics [8]. However, it has been shown that a macrospin approximation cannot always capture the complicated physics arising from incoherent switching [33], such as sub-volume excitation [37,38], anomalous branching of write error variation with increasing write voltage or current [21], and effects coming from higher-order spin wave modes [9]. Thus, full micromagnetic simulations may be needed for a more accurate study.…”
Section: Introductionmentioning
confidence: 99%
“…Since an error-rate calculation using brute force micromagnetic simulation can be computationally exhaustive, we have restricted simulations to only 1000 trials that gave an error rate of <10 −3 . The recently developed “rare-event enhancement” (REE) technique for micromagnetics 58 cannot be trivially applied to our fast picosecond magnetization switching dynamics. Hence, to capture the extreme tails of error-rate, we use a less computationally intensive equivalent single domain stochastic LLG simulation for the SW detector 46 and the “rare-event enhancement” (REE) technique to reach an error-rate of less than 10 −9 .…”
Section: Methodsmentioning
confidence: 99%
“…In logic, errors propagate and consequently the switching error probability of a switch should be less than 10 -15 for logic applications [14]. Memory is more forgiving since errors do not propagate, but in order to avoid repetitive write/read/re-write operations, the error probability still needs to be below 10 -9 [15]. Such low error probabilities may be out of reach for voltage-controlled binary nanomagnetic switches, and maybe a tall order for even currentcontrolled (more dissipative) ones if we wish to expend no more than ~1 fJ of write energy per bit.…”
Section: Introductionmentioning
confidence: 99%